Synthesis of ï§-Al2O3 Catalyst Support from Kaolin of Indonesian Origin - Tjokorde Walmiki Samadhi; Subagjo Subagjo; Kevin R. Lismana; Khasin Fuadi (Institute for Research and Community Services, Institut Teknologi Bandung, 2011)
Kaolin has been identified as a potential raw material for the production of ï§-Al2O3 for hydrotreating catalyst support. This work explores the technical feasibility of applying the potassium hydroxide (KOH) e xtraction synthesis route on kaolin from the Belitung Island in Indonesia. The application of a published synthesis method to Belitung kaolin requires an approximately twofold increase in kaolin calcination time, an increase in kaolin calcination temperature from 950 to 1000 °C, and a tenfold increase in metakaolin extraction time, to obtain a specific surface area higher than 200 m2/g. The highest specific surface area of 233 m2/g was obtained when the kaolin was calcined at 1000 °C for 24 hours, and the metakaolin was extracted by concentrated KOH solution for 12 hours. Phase characterization of the final product confirmed the formation of ï§-Al2O3, but with the inclusion of low-surface area ï¡-Al2O3 phase.